"Let Us Be Giants": Masculinity Nostalgia and Military Edutainment in South Asian War Comics. Issue 1 (1st June 2021) - Pirzada, Tehmina
Abstract: Since 2003, a budding collection of English-language war comics dealing with military conflicts between India and Pakistan have become part of the comic book repertoire in both countries. This article focuses on two such comics, Siachen (2012) and Haider (2015). Drawing upon Raewyn Connell's theorization of hegemonic masculinity, the article analyzes how the masculine role models depicted in Haider and Siachen vehemently deny the horrific emotional and physical costs of warfare. By examining hegemonic masculinity in the comics through masculinity nostalgia, and through close reading of the characters' physical appearances and their shared military camaraderie, this article establishes how the comics endorse militancy and warfare for the purpose of entertainment and education, thereby serving as military propaganda, regardless of the creators' personal intent.